A new species of Diadumene (Actiniaria: Diadumenidae) from the subtropical coast of Brazil - Beneti, Julia S.; Stampar, Sérgio N.; Maronna, Maximiliano M.; Morandini, André Carrara; Silveira, Fábio Lang Da (Zootaxa, 2015)
Diadumene paranaensis n. sp., collected from the Yacht Club of Paranaguá (Paranaguá Bay, Paraná State, southern Brazil), is described as a new species of sea anemone, based on external and internal morphology, cnidome, and molecular data for 16S/CO3 mitochondrial DNA. This species is partially similar to D. cincta due to the presence of macrobasic p-amastigophores in the tentacles, but is distinguished by the cinclides arranged in longitudinal rows and microbasic p-amastigophores in the acontia.